Preparation and Morphological Characteristics of Fluoroelastomer Electrospun Fibers - Kim, S.; Basuli, U.; Lee, R.H.; Gent, A.N.; Nah, C. (Asian Journal of Chemistry, 2013)
Electrospinning is a unique and versatile process for fabricating ultrathin fibers in the form of nonwoven mashes or as oriented arrays from a range of polymers. In this study, a fluoroelastomer mat was prepared by electrospinning and then irradiated with UV radiation for crosslinking. The electrospinning of fluoroelastomer produced nonwoven uniform layers of fibers. The prepared fluoroelastomer mat exhibited reasonably good mechanical properties. Morphological analyses showed that the fibers were small in diameter with a more regular fiber distribution. An ion-transportable stretchable membrane was prepared from these fluoroelastomer mats via a direct sulfonation reaction. The structural properties of these individual and sulfonated nanofibers mats were compared using scanning electron microscopy and Fourier transform infrared spectroscopy.